Observation of an anchoring transition in a discotic liquid crystal - VIJ, JAGDISH KUMAR; PEROVA, TANIA (EDP Sciences, 1998)
We report the anchoring transition in a discotic liquid crystal, hexapentyloxytriphenylene (HPT), from edge-on to side-on alignment in a discotic phase. The topology, easy direction of orientation and the coating of the substrate with a polymer are the determining factors for the alignment and the anchoring transition in a discotic liquid crystal.
PUBLISHED
Keywords: Mechanical and Manufacturing Engineering